2015
DOI: 10.1016/j.bbagen.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The Nav1.2 channel is regulated by GSK3

Abstract: Background Phosphorylation plays an essential role in regulating the voltage-gated sodium (Nav) channels and excitability. Yet, a surprisingly limited number of kinases have been identified as regulators of Nav channels. Herein, we posited that glycogen synthase kinase 3 (GSK3), a critical kinase found associated with numerous brain disorders, might directly regulate neuronal Nav channels. Methods We used patch-clamp electrophysiology to record sodium currents from Nav1.2 channels stably expressed in HEK-293… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 52 publications
0
47
1
Order By: Relevance
“…As a result, these studies revealed a network of kinases centered on GSK–3 that modulate the FGF14:Nav channel complex bidirectionally (Hsu et al, 2015). As shown previously, pharmacological inhibition and/or silencing of GSK–3 suppresses the interaction of FGF14 with Nav1.6 and Nav1.2 channels, modulates the functional activity of FGF14 on Na + currents, and control the sub-cellular distribution and co-localization of the two proteins in the axon and the somatodendritic compartment, phenotypes that might contribute to the role of GSK–3 in regulating neuronal excitability in the brain (James et al, 2015; Shavkunov et al, 2013; Laezza et al, 2007, 2009). These studies highlight the potential of using protein complementation assays to assess signaling pathways, a method that has been extended in the current study through the identification of a novel pathway that controls FGF14 function.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…As a result, these studies revealed a network of kinases centered on GSK–3 that modulate the FGF14:Nav channel complex bidirectionally (Hsu et al, 2015). As shown previously, pharmacological inhibition and/or silencing of GSK–3 suppresses the interaction of FGF14 with Nav1.6 and Nav1.2 channels, modulates the functional activity of FGF14 on Na + currents, and control the sub-cellular distribution and co-localization of the two proteins in the axon and the somatodendritic compartment, phenotypes that might contribute to the role of GSK–3 in regulating neuronal excitability in the brain (James et al, 2015; Shavkunov et al, 2013; Laezza et al, 2007, 2009). These studies highlight the potential of using protein complementation assays to assess signaling pathways, a method that has been extended in the current study through the identification of a novel pathway that controls FGF14 function.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, we hypothesized that changes in phosphorylation of residues at the FGF14 C-tail could affect the interaction with Nav channels. Our previous research has shown that GSK–3, a multifunctional kinase important for neuronal survival, cellular signaling, and stress response (Jope et al, 2007; Jope & Roh, 2006; Wu et al, 2013; Chen et al, 2011; Kim & Snider, 2011) and dysregulated in a number of AD and psychiatric disorders (Emamian, 2012; Jope et al, 2007; Jope & Roh, 2006; Liu et al, 2013; Budni et al, 2012; Scala et al, 2015; Maqbool et al, 2016; Morris & Berk, 2016; Provensi et al, 2016; Avila et al, 2010) affecting cognition, including depression and bipolar disorder (Gould et al, 2004; Koros & Dorner-Ciossek, 2007; Omata et al, 2011), critically modifies the interaction, assembly, localization, and activity of FGF14 and Nav channels (Hsu et al, 2015; James et al, 2015; Shavkunov et al, 2013). Furthermore, we observed that the C-tail of FGF14 contains a consensus GSK–3 phosphorylation motif ( S/T )XXX(S/T), the first residue in this sequence corresponding to S226.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations